2011
DOI: 10.1186/1477-7819-9-145
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of primitive gastro-intestinal lymphomas: a systematic review

Abstract: Primitive Gastrointestinal Lymphomas (PGIL) are uncommon tumours, although time-trend analyses have demonstrated an increase. The role of surgery in the management of lymphoproliferative diseases has changed over the past 40 years. Nowadays their management is centred on systemic treatments as chemo-/radio- therapy. Surgery is restricted to very selected indications, always discussed in a multidisciplinary setting. The aim of this systematic review is to evaluate the actual role of surgery in the treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…Several studies have shown no differences in survival for patients treated with chemotherapy and/or radiation therapy alone vs surgery plus chemotherapy and/or radiation therapy . A meta‐analysis of five studies containing a total of 701 patients with PGINHL revealed no differences in OS at 10 years between patients treated with chemotherapy and/or radiation therapy compared to patients treated surgically (HR 0.61, 95% CI 0.26‐1.41, P = .25); however, patients treated with chemotherapy and/or radiation therapy alone had superior disease‐free survival (OR 0.17, 95% CI 0.08‐0.37, P < .00001) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown no differences in survival for patients treated with chemotherapy and/or radiation therapy alone vs surgery plus chemotherapy and/or radiation therapy . A meta‐analysis of five studies containing a total of 701 patients with PGINHL revealed no differences in OS at 10 years between patients treated with chemotherapy and/or radiation therapy compared to patients treated surgically (HR 0.61, 95% CI 0.26‐1.41, P = .25); however, patients treated with chemotherapy and/or radiation therapy alone had superior disease‐free survival (OR 0.17, 95% CI 0.08‐0.37, P < .00001) …”
Section: Discussionmentioning
confidence: 99%
“…7,[9][10][11][12][13][14] A meta-analysis of five studies containing a total of 701 patients with PGINHL revealed no differences in OS at 10 years between patients treated with chemotherapy and/or radiation therapy compared to patients treated surgically (HR 0.61, 95% CI 0.26-1.41, P = .25); however, patients treated with chemotherapy and/or radiation therapy alone had superior disease-free survival (OR 0.17, 95% CI 0.08-0.37, P < .00001). 15 Several studies have shown a survival benefit for surgery and chemotherapy/radiation therapy compared to chemotherapy and/or radiation therapy alone. [16][17][18][19][20][21] The largest of these trials was a retrospective study of 345 patients with GI DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…The literature also showed a decrease in the role of primary surgery for primary gastric NHL. It has been shown that surgery should be reserved for the treatment of patients who present with disease complications, such as bleeding or perforation, due to the innate morbidity of surgery (15)(16)(17)(18)(19). Our study was designed to explore whether the introduction of rituximab and the decreasing rates of primary surgery influenced early mortality in patients with gastric DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…Although surgery can clearly result in excellent survival for patients with localized disease, it is associated with both short-term and long-term morbidity. Therefore, surgical treatment is generally reserved for the treatment of complications, such as occlusion, bleeding or perforation [17]. In cases of localized disease, excellent control can be also obtained with radiation therapy.…”
Section: Discussionmentioning
confidence: 99%